Interactive marketing and relationship quality in Islamic banking: A Parepare case study - Addury, Multazam Mansyur; Pangestu, Dian Resky (Faculty of Business & Economics, Universitas Islam Indonesia, 2023)
Purpose − This research aims to analyze the effects of interactive marketing and relationship quality on customer satisfaction and loyalty in Islamic banking.Methodology − A quantitative research approach was employed, and data was collected through a survey questionnaire administered to customers of Islamic banks in Parepare. The data analysis method used in this study is Partial Least Squares-Structural Equation Modeling (PLS-SEM).Findings − The study findings indicate that, indirectly, interactive marketing and relationship quality do not have a direct significant influence on customer loyalty in Islamic banks. However, it is observed that interactive marketing and relationship quality can affect customer loyalty through satisfaction. These findings suggest that the process of maintaining and enhancing customer loyalty in Islamic banks requires careful attention to multiple factors and stages.Implications − This research emphasizes the significance of integrating interactive marketing strategies, fostering relationship quality, and prioritizing customer satisfaction in the context of Islamic banks. These factors are essential for maintaining and strengthening customer loyalty, ultimately contributing to the long-term success and competitiveness of Islamic banks in Kota Parepare.Originality − The originality of this research lies in its contextual focus and integration of variables. Firstly, the study specifically examines the impact of interactive marketing and relationship quality on customer satisfaction and loyalty within the context of Islamic banks in Kota Parepare. Secondly, the study integrates multiple variables, including interactive marketing, relationship quality, customer satisfaction, and customer loyalty, providing a comprehensive understanding of the factors that contribute to customer loyalty in the context of Islamic banks.